Metabolic Acidosis in an Infant Associated with Permethrin Toxicity. Issue 1 (9th December 2014) - Goksugur, Sevil B.; Karatas, Zehra; Goksugur, Nadir; Bekdas, Mervan; Demircioglu, Fatih
Abstract Pyrethroids are broad‐spectrum insecticides. Permethrin intoxication due to topical application has not been documented in humans. We report a 20‐month‐old infant who had used 5% permethrin lotion topically for scabies treatment. Approximately 60 mL (20 mL/day) was used and after the third application he developed agitation, nausea, vomiting, respiratory distress, tachycardia, and metabolic acidosis. His clinical symptoms and metabolic acidosis normalized within 20 hours. His follow‐up was unremarkable. Toxicity of permethrin is rare, and although permethrin is a widely and safely used topical agent in the treatment of scabies and lice, inappropriate use may rarely cause toxicity. Moreover, in cases of unexplained metabolic acidosis, topically applied medications should be carefully investigated.